A study of the factors that influence compositions of common texts with an emphasis regarding the text of Te Deum settings by Antonín Leopold Dvořák and Franz Joseph Haydn - Bogner, Ryan (Kansas State University, 2011)
The Te Deum chant began in the Roman Catholic Church in prayer, and like many other psalms used in the Mass, it has evolved into a concert piece with settings composed for coronations, military victories, and other festive occasions. This author has identified two significant settings of this text by Joseph Franz Haydn and Antonín Leopold Dvořák for this discussion to study how common factors (primarily a common text) influence their compositions. Chapter I provides the purpose of the study, a brief description of related research, description of the appendices, and analytical criteria for examining the Te Deum settings. Chapter II presents a study of the ancient Te Deum psalm and its text. Topics for discussion include a brief overview of the history of chant. In regards to the Te Deum, further studies are included on its history, uses within prayer, the text, melody, and other uses of the Te Deum. Chapter III contains an in-depth analysis of the Haydn Te Deum (HXXIIIc:2) and the Dvořák Te Deum (Op. 103, B176, [Op. 93, Op. 98]). Analytical criteria for examining these settings consist of: a brief biographical sketch along with each composers compositional characteristics and reasons for commissioning this piece; discussions on general characteristics, structural and formal design, themes, melodic/harmonic characteristics, rhythmic/metrical/tempo characteristics, articulations, dynamics, texture, performance, pedagogical, and conducting considerations. Chapter IV summarizes general trends in the usage of the text of Te Deum. Information for this final chapter is derived from the in-depth analysis, the ancient history of the Te Deum, and other settings of the Te Deum text examined in sources similar to this document. The findings contain summaries of the musical elements listed above as well as general and specific commonalities of textual influence between the selected Te Deum settings. Appendix A provides the complete text of the Te Deum psalm with English translations and melody. Appendix B provides a score analysis of Te Deum (HXXIIIc:2). Appendix C provides a score analysis of Te Deum (Op. 103, B176, [Op. 93, Op. 98]).
Keywords: Te Deum; Haydn; Dvořák; Joseph Haydn; Antonín Dvořák; Op. 103, B176; Music (0413); Musical Performances (0943); Music Education (0522)